FRI0323 THE PRESENCE OF SPONDYLOARTHRITIS IS ASSOCIATED WITH HIGHER CLINICAL DISEASE ACTIVITY IN PATIENTS WITH EARLY CROHN'S DISEASE: RESULTS OF A PROSPECTIVE COHORT STUDY. (2nd June 2020) - Rios Rodriguez, V.; Protopopov, M.; Proft, F.; Lüders, S.; Rademacher, J.; Haibel, H.; Verba, M.; Sieper, J.; Sonnenberg, E.; Schumann, M.; Kredel, L. I.; Siegmund, B.; et al.
Abstract : Background: Inflammatory bowel disease (IBD) and specifically Crohn's disease (CD) is known to be associated with spondyloarthritis (SpA). However, only little is known about factors associated with the development of spondyloarthritis in CD. Objectives: To identify factors associated with the presence of SpA in a cohort of patients with CD. Methods: Patients with a definite diagnosis of CD naïve to or not being treated with biological agents for at least 3 months were included in a CD-arm of the German Spondyloarthritis Inception Cohort (GESPIC-Crohn). Gastroenterologists were encouraged to include consecutively recently diagnosed CD patients. Patients were classified according to the Montreal classification including location and behavior of CD. Patients received a structured assessment of SpA manifestations (including magnetic resonance imaging of sacroiliac joints and spine) by a rheumatologist who was responsible for the final diagnosis of SpA / no SpA. Clinical activity of CD was assessed by the Harvey-Bradshaw Index (HBI). In addition, colonoscopy was performed, Simple endoscopic Score for Crohn's Disease (SES-CD) was determined and fecal calprotectin was measured. Results: A total of 108 patients with CD were enrolled. The mean (mean ± SD) age was 36.6 ± 12.7 years, and CD symptom duration was 5.3 ± 7.4 years. At baseline, 44 (40.7%) patients were treated with non-biologic immunomodulating drugs: 16 (14.8%) patients received mesalazine, 27 (25.0%) azathioprine, and 1 (0.9%) methotrexate. Oral steroids were given to 38 (35.2%) patients. A total of 103 (96.3%) patients were biologics naïve. SpA was diagnosed in 23 (21.3%) patients: 12 had axial SpA and 11 peripheral SpA. Patients with SpA had higher prevalence of HLA-B27, of clinical SpA features (back pain, inflammatory back pain, peripheral arthritis, enthesitis), higher level of CRP and higher activity of CD as measured by the HBI. There were not substantial differences between SpA vs. non-SpA patients in terms of CD duration, endoscopic activity, disease location or behavior, or treatment, except for mesalazine, which was more frequently administered in patients with SpA than non-SpA (39.1% vs. 8.2%, p=0.001, respectively). Conclusion: SpA was present in 21% of patients with CD in this early cohort with almost equal proportions of axial and peripheral forms. Presence of HLA-B27 and higher clinical activity of CD were associated with the presence of SpA. Disclosure of Interests: Valeria Rios Rodriguez Consultant of: Abbvie, Novartis, Mikhail Protopopov Consultant of: Novartis, Fabian Proft Grant/research support from: Novartis Pharma GmbH, Consultant of: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Susanne Lüders: None declared, Judith Rademacher: None declared, Hildrun Haibel Consultant of: Abbvie, Jansen, MSD, and Novartis, Speakers bureau: Abbvie, Jansen, MSD, and Novartis, Maryna Verba: None declared, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Elena Sonnenberg: None declared, Michael Schumann: None declared, Lea Isabell Kredel: None declared, Britta Siegmund Consultant of: Abbvie, Boehringer, Celgene, Falk, Janssen, Lilly, Pfizer, Prometheus, Takeda, Speakers bureau: Abbvie, CED Service GmbH, Falk, Ferring, Janssen, Novartis, Takeda (BS served as representative of the Charité), Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB